Socialism and the diasporic 'other' : a comparative study of Irish Catholic and Jewish radical and communal politics in East London, 1889-1912 - Renshaw, Daniel (Studies in labour history (Liverpool University Press), 2018)
Socialism and the Diasporic 'Other' examines the relationship between the London-based Left and Irish and Jewish communities in the East End between 1889 and 1912. Using a comparative framework, it examines the varied interactions between working class diasporic groups, conservative communal hierarchies and revolutionary and trade union organisations.